Potential Improvement of Environmental Quality Index (EQI) Based on District Level Data. Case Study in Bekasi Regency - Arief Budi Kusuma; Hariadi Kartodihardjo; Yudi Setiawan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Bekasi Regency always experiences an increase in population every year that significantly affects the Environmental Quality Index (EQI) in Bekasi Regency. Environmental Quality Index (EQI) is a value that can describe the quality of the environment in an area at a specified time. The Regency Environmental Quality Index (EQI) is a composite of the Water Quality Index (WQI), Air Quality Index (AQI), and Land Quality Index (LQI). All Environmental Quality Indexes positively affect the fulfilment of basic needs. The calculations in this research show the Environmental Quality Index (EQI) Based on District Level Data in Bekasi Regency is 47.56.